Calculation of adsorption and interaction mechanisms of O₂ and CO₂ molecules on BaTiO₃ surface - Sejkovskij, I.D.; Zhiharev, V.N.; Popik, Yu.V. (Condensed Matter Physics, 2003)
The paper presents the results of quantum chemical calculations using
the extended Huckel method for adsorption of O₂ and CO molecules on
BaTiO₃ surface. It is shown that on (001) surface, the physical adsorption
is dominant, whereas on (002) surface the chemical adsorption prevails,
the Ti ions being the most active adsorption centres. The possible dissociation
mechanisms of the adsorbed oxygen molecule and a heterogeneous
oxidation reaction of CO in CO₂ are considered. У роботі наведено результати квантово-хімічних розрахунків розширеним методом Хюккеля адсорбції молекул O₂, CO₂, CO та атомів
O і C на поверхні BaTiO₃. Показано, що на поверхні (001) переважає
фізична адсорбція, а на поверхні (002) – хімічна, причому найбільш
активними центрами адсорбції є іони Ti. Розглянуті можливі механізми дисоціації адсорбованих молекул кисню і гетерогенної реакції
окислення CO в CO₂.